1985
DOI: 10.1002/jmor.1051850105
|View full text |Cite
|
Sign up to set email alerts
|

Muscle system organization in the echinoderms: II. Microscopic anatomy and functional significance of the muscle‐ligament‐skeleton system in the arm of the comatulids (Antedon mediterranea)

Abstract: Comatulids are able to perform quick and complex movements of the arms which are used to swim, creep, walk, and also form a rigid, feeding-filtration fan. To perform such versatile movements, the arms of these animals are equipped with a classical endoskeletal system, with joints, muscles, ligaments, and a hydroskeleton of three different coelomic channels. Light microscopic study of the detailed anatomical organization of the arm clarifies both the complex relations between the parts involved in the movements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Instead, both these workers conclusively demonstrated that the aboral and not the oral nerve mediates swimming behavior. The wounds made by Carpenter and Marshall were relatively small and thus do not conclusively refute the idea of Candia Carnivali and Saita (1985) that hydrostatic pressure extends the feather star arm. According to these last authors, the coelomic canals become constricted by intrinsic muscles at intervals along the length of the arm and hydrostatic pressure then builds up in the lumen of each canal segment, alternating with the constrictions; as already mentioned, this pressure results from contractions of intrinsic muscles in the canal walls and extrinsic muscles in the surrounding tissues.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Instead, both these workers conclusively demonstrated that the aboral and not the oral nerve mediates swimming behavior. The wounds made by Carpenter and Marshall were relatively small and thus do not conclusively refute the idea of Candia Carnivali and Saita (1985) that hydrostatic pressure extends the feather star arm. According to these last authors, the coelomic canals become constricted by intrinsic muscles at intervals along the length of the arm and hydrostatic pressure then builds up in the lumen of each canal segment, alternating with the constrictions; as already mentioned, this pressure results from contractions of intrinsic muscles in the canal walls and extrinsic muscles in the surrounding tissues.…”
Section: Discussionmentioning
confidence: 79%
“…The coelomic spaces in the arm are the water canal, the genital canal, the subtentacular canal and the aboral canal (the detailed, three-dimensional topography of these coeloms is illustrated in Grimmer and Holland 1979). The subtentacular and aboral canals are the coeloms that are most important for the hydraulic extension mechanism proposed by Candia Carnivali and Saita (1985). After our gouging operation on the proximal half of each arm LM and SEM showed that we had removed the soft tissues oral to the dashed line in Fig.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations